Crystal structures of N, N′-bis(thiophen-2-ylmethyl)ethane-1, 2-diaminium hydrochloride and of its [AuCl4]− salt solved by powder diffraction. Issue 3 (15th August 2014) - Silva, Silvioney A.; Masciocchi, Norberto; Cuin, Alexandre
Abstract : Preparation, analytical characterization, and crystal structures of N, N ′-bis(thiophen-2-ylmethyl)ethane-1, 2-diaminium hydrochloride (1) and of its gold derivative, N, N ′-bis(thiophen-2-ylmethyl)ethane-1, 2-diaminium tetrachloroaurate(III) (2) are reported. Compound (1) was obtained by reduction of the Schiff base N, N ′-bis(thiophen-2-ylmethyl)ethane-1, 2-diamine followed by HCl solution addition, whereas compound (2) was prepared reacting (1) with K[AuCl4 ] in aqueous solution. Compound (1) crystallizes in the orthorhombic system with space group Iba 2 and cell parameters a = 29.856(1), b = 5.1372(2), and c = 10.1635(4) Å. Crystals of (2) belong to the monoclinic system with space group P 21 / c and cell parameters a = 11.0829(1), b = 9.5852(1), c = 11.6054(2) Å, and β = 75.49(1)°. Both structures contain diprotonated organic moieties, counterbalanced by hydrogen-bonded Cl −, or [AuCl4 ] − ions, in compounds (1) and (2), respectively.